IMPLIKASI PEMBELAJARAN DARING TERHADAP NILAI KARAKTER QUR’ANI PESERTA DIDIK SMK YANINDO JAKARTA: IMPLIKASI, PEMBELAJARAN DARING DAN KARAKTER QUR'ANI - Muammar Qadafi, (JOEL: Journal of Educational and Language Research, 2022)
The implications of online learning policies during the COVID-19 pandemic on the character of Yanindo Vocational High School students who are dominantly affected and clearly visible are the Qur'anic characters in the form of moral values ​​to God, morality to teachers and morals to fellow students, the value of responsibility, discipline, and honest. The role of parents is very important in the continuity of students' online learning, especially in anticipating the conveniences provided by online learning to the future. With this finding, it is hoped that it can be a material for reflection and evaluation of various parties, especially the three education centers in implementing online learning for elementary school students. In addition, this result is also expected to be a study material for further research in analyzing what other characters are affected by online learning even though they are not directly affected.